Composite copper foil

By using spherical support layer and multi-layer metal structure in composite copper foil, the problem of insufficient bonding force of copper foil is solved, the binding force and flow diversion capacity is improved, the risk of processing damage and total quality is reduced, and more efficient Battery performance.

CN119252932APending Publication Date: 2025-01-03SHENZHEN JINJIA JUNENG TECH CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411250717.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

The bonding force of the existing composite copper foil is weak and the support layer is easily stretched and damaged during processing. The existing improvement plan is expensive, complicated process and poor effect.

Method used

Using a copper foil with spherical crystals on the support layer, the metal layer combines with spherical crystals on the support layer through multiple nanoscale particles to enhance binding force, and optimizes flow diversion capacity and tensile strength through multi-layer structural design, including nickel-chromium alloy and copper. The clamping of alloy layer, optimization of thickness and surface density.

Benefits of technology

The bonding force and flow diversion capacity of copper foil are improved, the tensile strength is enhanced, the risk of damage in subsequent processing is reduced, and the total quality and cost are reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119252932A_ABST
    Figure CN119252932A_ABST
Patent Text Reader

Abstract

The composite copper foil comprises a supporting layer, a metal layer is arranged on the surface of the supporting layer, the supporting layer is provided with crystals, the crystal form of the crystals of the supporting layer is spherocrystal, the average particle size of the crystals of the supporting layer is larger than that of the metal layer, and the average particle size of the crystals of the supporting layer is larger than that of the metal layer. And copper metal or copper alloy is arranged in the metal layer. The metal layer can be in bonding contact with the spherocrystal of the supporting layer through a plurality of nanoscale particles, the acting force between particle molecules of the metal layer and molecules of the supporting layer is increased, the bonding strength can be improved, and therefore the bonding force between the metal layer and the supporting layer can be improved; meanwhile, the contact among metal layer particle molecules is increased, the overall sheet resistance of the metal layer is reduced, the flow conductivity of the metal layer is improved, the tensile strength of the metal layer is improved due to the fact that the contact among the metal layer molecules is large, and the composite copper foil is not prone to being stretched and damaged in the follow-up processing link.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of current collectors, and in particular to a composite copper foil. Background Art

[0002] In the field of batteries, especially in lithium-ion batteries, current collectors are one of the indispensable components. It mainly refers to metal foils, such as copper foil and aluminum foil, which can carry active materials in the battery and collect the current generated by the active materials to form a larger current output. The function of the current collector is to accelerate the transfer of charge electrons, reduce the polarization phenomenon in the electrochemical reaction, improve the charging and discharging efficiency, and accelerate the insertion / extraction reaction of lithium ions. The ideal lithium-ion battery current collector should meet the following conditions: high conductivity, good chemical and electrochemical stability, high mechanical strength, good compatibility and binding force with electrode active materials, cheap and easy to obtain, and light weight. However, in practical applications, different current collector materials still have some problems and cannot fully meet all the above conditions. For example, copper is easily oxidized at a higher potential, so it is suitable for use as a negative electrode current collector; while aluminum has a more serious corrosion problem when used as a negative electrode current collector, so it is more suitable for use as a positive electrode current collector.

[0003] In addition, with the continuous development of technology, new materials such as composite current collectors are playing an increasingly important role in the battery industry. Composite current collectors combine the advantages of multiple materials, such as conductivity, corrosion resistance, mechanical strength, etc., to meet the needs of higher performance batteries. At present, composite copper foil is safer than pure copper foil when used in batteries to play the role of converging current. However, the current bonding force between the copper layer and the middle support layer of the composite copper foil is weak. There are many technical solutions to this problem, which are basically achieved by modifying the middle support layer. However, this method is expensive, the process is complicated, and the effect is not good. Therefore, the existing technology needs to be improved and improved. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, an object of the present invention is to provide a composite copper foil.

[0005] In order to solve the above technical problems, the present invention adopts the following technical solutions:

[0006] The present invention provides a composite copper foil, comprising a support layer, a metal layer is arranged on the surface of the support layer, the support layer has crystals, the crystal shape of the crystals of the support layer is spherulites, the average particle size of the crystals of the support layer is greater than the average particle size of the particles of the metal layer, and the metal layer contains copper metal or copper alloy.

[0007] Furthermore, in the composite copper foil, the metal layer includes a first metal sublayer and a second metal sublayer, and the first metal sublayer is sandwiched between the support layer and the second metal sublayer.

[0008] Furthermore, in the composite copper foil, the average particle size of the crystals of the support layer is 3-5 times the average particle size of the metal layer. At the same time, the surface density of the metal layer is 2.1kg / m2-3kg / m2, and the support layer is a film with a crystallinity of 60%-70%.

[0009] Furthermore, in the composite copper foil, the surface density of the first metal sublayer is greater than the surface density of the second metal sublayer.

[0010] Furthermore, in the composite copper foil, the first metal sublayer is a nickel-chromium alloy layer or a copper alloy layer.

[0011] Furthermore, in the composite copper foil, the first metal sublayer is a nickel-chromium alloy layer or a nickel-copper alloy layer, and the second metal sublayer is a metal copper layer.

[0012] Furthermore, in the composite copper foil, the thickness of the first metal sublayer is 30nm-100nm, and the thickness of the second metal sublayer is 900nm-1000nm.

[0013] Furthermore, in the composite copper foil, the thickness of the support layer is 3um-8um, the first metal sublayer is a magnetron sputtering layer, and the second metal sublayer is a magnetron sputtering layer.

[0014] Furthermore, in the composite copper foil, the support layer is a thin film with a crystallinity of 50%-70%, and the mass of the metal layer is less than the mass of the support layer.

[0015] Specifically, in the composite copper foil, the supporting layer is a film formed by one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride polymer materials, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, and phenolic resin.

[0016] Compared with the prior art, the present invention provides a composite copper foil, including a support layer, a metal layer is arranged on the surface of the support layer, the support layer has crystals, the crystal shape of the crystals of the support layer is spherulites, the average particle size of the crystals of the support layer is greater than the average particle size of the metal layer, and the metal layer contains copper metal or copper alloy. The metal layer of the present invention can be bonded and contacted with the spherulites of the support layer through a plurality of nano-scale particles, which increases the interaction between the metal layer particle molecules and the support layer molecules, which is beneficial to improve the bonding strength, thereby improving the bonding force between the metal layer and the support layer. At the same time, since the crystal shape of the support layer is spherulites, the contact between the metal layer particle molecules is also increased, the overall square resistance of the metal layer is reduced, and the flow conductivity of the metal layer is improved. Since there are many contacts between the metal layer molecules, it is beneficial to improve the tensile strength of the metal layer, so that the composite copper foil of the present invention is not easily damaged by stretching in subsequent coating and other processing links. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.

[0018] Figure 1 This is a schematic structural diagram of the composite copper foil provided by the present invention.

[0019] Description of the accompanying drawings: support layer 100; metal layer 200; first metal sub-layer 210; second metal sub-layer 220. DETAILED DESCRIPTION

[0020] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0022] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or suggesting their relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the technical solutions between the various embodiments can be combined with each other, but they must be based on the ability of ordinary technicians in the field to implement them. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.

[0023] like Figure 1 As shown, a composite copper foil provided by the present invention includes a support layer 100, a metal layer 200 is arranged on the surface of the support layer 100, the support layer 100 has crystals, the crystal shape of the crystals of the support layer 100 is spherulites, the average particle size of the crystals of the support layer 100 is larger than the average particle size of the particles of the metal layer 200, and the metal layer 200 contains copper metal or copper alloy. The metal layer 200 of the present invention can be bonded and contacted with the spherulites of the support layer 100 through a plurality of nano-scale particles, which increases the interaction force between the metal layer 200 particle molecules and the support layer 100 molecules, and is conducive to improving the bonding strength, thereby improving the bonding force between the metal layer 200 and the support layer 100. At the same time, since the crystal form of the support layer 100 is spherulites, the contact between the metal layer 200 particle molecules is also increased, the overall square resistance of the metal layer 200 is reduced, and the flow conductivity of the metal layer 200 is improved. Since there are many contacts between the metal layer 200 molecules, it is conducive to improving the tensile strength of the metal layer 200, so that the composite copper foil of the present invention is not easily damaged by stretching in subsequent processing links such as coating. Further, in the composite copper foil provided by the present invention, the metal layer 200 includes a first metal sublayer 210 and a second metal sublayer 220, and the first metal sublayer 210 is sandwiched between the support layer 100 and the second metal sublayer 220.

[0024] Further, in the composite copper foil provided by the present invention, the first metal sublayer 210 is a nickel-chromium alloy layer or a copper alloy layer. Further, in the composite copper foil provided by the present invention, the first metal sublayer 210 is a nickel-chromium alloy layer or a nickel-copper alloy layer, and the second metal sublayer 220 is a metal copper layer. Specifically, in the composite copper foil provided by the present invention, the thickness of the first metal sublayer 210 is 30nm-100nm, and the thickness of the second metal sublayer 220 is 900nm-1000nm. The thickness of the first metal sublayer 210 is 30nm-100nm, such as 50nm, which can reduce the weight of the composite copper foil. The second metal sublayer 220, that is, the metal copper layer, has a thickness of 900nm-1000nm, such as 950nm. The second metal sublayer 220 in this thickness range can ensure the conductive performance of the composite copper foil on the one hand, and prevent the support layer 100 from becoming brittle on the other hand. If the thickness of the metal copper layer is higher, the number of times of coating is higher, then the probability of the support layer 100 becoming brittle is greater.

[0025] The processing of the metal copper layer mainly adopts the means of vacuum coating, and vacuum coating mainly includes two methods: vacuum evaporation and magnetron sputtering. Among them, vacuum evaporation is a physical phase deposition (PVD) method, which melts the metal into a liquid state, forms metal vapor and begins to volatilize, and then condenses the copper atoms in the vapor to deposit and grow on the surface of the polymer material. In this process, the temperature of the molten metal is very high, and the temperature of the gaseous metal formed (the present invention is a composite copper foil, such as forming gaseous metal copper) is very high, and the support layer 100 is easy to become brittle at high temperature. Magnetron sputtering refers to the use of plasma generated by rare gas to bombard the surface of the cathode copper target under the action of electric and magnetic fields, and then sputter out the molecules, atoms, ions and electrons on the surface of the target, and the sputtered particles are shot toward the surface of the target in a certain direction, and then the target surface forms a coating. When the magnetron is used, the plasma bombardment will also generate high temperature, which is also easy to make the support layer 100 brittle. The composite copper foil of the present invention can be prepared by a variety of methods. When preparing the composite copper foil of the present invention, the support layer 100 can be first taken, and then the desired thickness of the first metal sublayer 210 and the second metal sublayer 220 can be formed on the support layer 100. In this embodiment, the first metal sublayer 210 is formed on the support layer 100, and the first metal sublayer 210 can be formed on the support layer 100 by magnetron sputtering. At this time, a target material containing the material of the first metal sublayer 210 is placed in the vacuum chamber of the vacuum coating equipment, and magnetron sputtering is performed on the upper and lower surfaces of the support layer 100, so as to obtain the first metal sublayer 210. In this embodiment, the metal copper layer can form the second metal sublayer 220 on the first metal sublayer 210 by magnetron sputtering, and magnetron sputtering is performed using a copper target, so as to form the second metal sublayer 220 on the first metal sublayer 210.

[0026] In other embodiments, the second metal sublayer 220 can also be formed by multiple steps, such as first forming a thickening layer (that is, an additional first metal sublayer 210) on the first metal sublayer 210 by magnetron sputtering, thickening the first metal sublayer 210, and then forming the second metal sublayer 220 on the thickening layer by electroplating. The electroplating process of metal copper is a series of complex electrochemical reactions, through which a uniform and dense metal copper plating layer is deposited on the surface of the first metal sublayer 210. Metal copper electroplating is a process of depositing a thin copper film on the surface of an object using the principle of electrolysis. This process requires precise control of multiple parameters to ensure the quality and performance of the coating. In specific preparation, for example, the electroplating solution is usually composed of a common copper electroplating solution mainly composed of a copper salt (such as copper sulfate), an acidic component (such as sulfuric acid) and chloride ions. Copper sulfate provides copper ions, sulfuric acid is used to adjust the conductivity and pH of the solution, and chloride ions help to improve the uniformity and adhesion of electroplating. The electrolyte needs to be prepared, and the preparation of the electroplating solution needs to be mixed strictly in proportion to ensure stability and efficiency during the electroplating process. For example, the ratio of copper sulfate and sulfuric acid usually needs to be adjusted according to the actual electroplating requirements. The surface of the first metal sublayer 210 needs to be cleaned in advance. In order to ensure that the metal copper can be evenly deposited on the surface of the first metal sublayer 210, the surface of the first metal sublayer 210 needs to be thoroughly cleaned to remove oil, oxide layer and other pollutants. In addition to the cleaning process, the surface of the first metal sublayer 210 needs to be activated, and the activity of the surface of the first metal sublayer 210 is increased by pickling or using other chemical reagents, thereby improving the adhesion of the metal copper coating. Of course, for some materials that are not easy to electroplate, pretreatment may also be required, such as depositing a conductive film on a non-metallic material. During the electroplating process, attention should be paid to the control of current density, which is an important factor affecting the quality of the copper coating. If the current density is too low, the copper deposition rate will be slow and the crystallization will be rough; if the current density is too high, it may cause the coating to burn or produce undesirable internal stress. The electroplating process should also pay attention to the temperature and stirring of the electroplating solution, which will also affect the quality and uniformity of the copper coating. Appropriate temperature and stirring can speed up the electroplating rate and improve the uniformity of the coating. After the electroplating is completed, the surface of the first metal sublayer 210 needs to be cleaned and dried. After the electroplating is completed, the workpiece needs to be cleaned with deionized water to remove the electroplating solution residue on the surface, and then dried. Thus, the second metal sublayer 220 is formed on the thickened layer by electroplating.

[0027] Preferably, in the composite copper foil provided by the present invention, the average particle size of the crystals of the support layer 100 is 3-5 times the average particle size of the particles of the metal layer 200, and the surface density of the metal layer 200 is 2.1kg / m2-3kg / m2. The support layer 100 of the present invention is a film (polymer), and the crystallinity of the film has an important influence on the performance of the material. Polymers with higher crystallinity usually have higher melting points, better heat resistance and mechanical properties, but may reduce the toughness and ductility of the material. Therefore, controlling the crystallinity of the film is an important means to optimize its performance. For the crystallinity of the film, polymers with good structural symmetry of the molecular chain, fewer side chains or small side groups are easy to be close to each other and easy to crystallize; high temperature can increase the activity of the polymer, thereby accelerating the crystallization rate; during the cooling process, if there is an external force, it can also promote the crystallization of the polymer; during the production process, the crystallinity of the crystalline plastic can be controlled by adjusting the injection pressure and the holding pressure; adding a nucleating agent can promote rapid crystallization at high mold temperature, eliminating the contradiction that low temperature is conducive to rapid nucleation but slows down grain growth. The crystallinity of the film directly affects its physical and chemical properties. By regulating the above factors, the performance of the film can be optimized to meet specific application requirements. In particular, in the production of lithium batteries, the crystallinity of copper foil as a current collector directly affects the performance and life of the battery. In the present invention, the support layer 100 is a film with a crystallinity of 60%-70%, and at the same time, the surface density of the metal layer 200 is 2.1kg / m2-3kg / m2. This is conducive to the composite copper foil metal layer 200 of the present invention having good bonding with the support layer 100, and the composite copper foil is better in terms of transparency and hardness. Further, in the composite copper foil provided by the present invention, the surface density of the first metal sublayer 210 is greater than the surface density of the second metal sublayer 220. In this way, when the current passes through, the current passes more from the second metal sublayer 220, reducing the heat generated by the first metal sublayer 210. Since the first metal sublayer 210 is in direct contact with the support layer 100, the influence of temperature on the support layer 100 is reduced.

[0028] Furthermore, in the composite copper foil provided by the present invention, the support layer 100 is a thin film with a crystallinity of 50%-70%. Such a support layer 100 can achieve a balance in flexibility, hardness and transparency. Sufficient flexibility allows the support layer 100 of the present invention to be successfully plated in a vacuum coating device, sufficient hardness prevents the surface of the support layer 100 from being easily scratched, and a certain degree of transparency allows the composite copper foil product to be convenient for the CCD visual inspection system to detect holes. The mass of the metal layer 200 is less than the mass of the support layer 100, which is conducive to a smaller total mass of the composite copper foil, so that the electrical device using the composite copper foil of the present invention, such as a lithium battery, can be lighter and have a higher energy density.

[0029] Furthermore, in the composite copper foil provided by the present invention, the thickness of the support layer 100 is 3um-8um. The support layer 100 has a thickness of 3um-8um, such as 5um, which can reduce the weight of the composite copper foil. Compared with metal copper, the support layer 100 is made of non-conductive material, which greatly improves safety performance. Specifically, in the composite copper foil provided by the present invention, the support layer 100 is a film formed by one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene oxide, polyphenylene sulfide, polyethylene glycol, polysulfur nitride polymer materials, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, and phenolic resin. The support layer 100 of the present invention can be a film made of a non-conductive material.

[0030] In summary, the present invention provides a composite copper foil, including a support layer, a metal layer is arranged on the surface of the support layer, the support layer has crystals, the crystal shape of the crystals of the support layer is spherulites, the average particle size of the crystals of the support layer is greater than the average particle size of the metal layer, and the metal layer contains copper metal or copper alloy. The metal layer of the present invention can be bonded and contacted with the spherulites of the support layer through a plurality of nano-scale particles, which increases the interaction between the metal layer particle molecules and the support layer molecules, which is beneficial to improve the bonding strength, thereby improving the bonding force between the metal layer and the support layer. At the same time, since the crystal shape of the support layer is spherulites, the contact between the metal layer particle molecules is also increased, the overall square resistance of the metal layer is reduced, and the flow conductivity of the metal layer is improved. Since there are many contacts between the metal layer molecules, it is beneficial to improve the tensile strength of the metal layer, so that the composite copper foil of the present invention is not easily damaged by stretching in subsequent coating and other processing links.

[0031] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.

Claims

1. A composite copper foil, characterized in that: It includes a support layer, a metal layer is arranged on the surface of the support layer, the support layer has crystals, the crystal shape of the crystals of the support layer is spherulites, the average particle size of the crystals of the support layer is larger than the average particle size of the metal layer, and the metal layer contains copper metal or copper alloy.

2. The composite copper foil according to claim 1, characterized in that: The metal layer includes a first metal sublayer and a second metal sublayer, wherein the first metal sublayer is sandwiched between the support layer and the second metal sublayer.

3. The composite copper foil according to claim 2, characterized in that: The average particle size of the crystals in the support layer is 3-5 times the average particle size of the particles in the metal layer. At the same time, the surface density of the metal layer is 2.1 kg / m 2 -3kg / m 2 The support layer is a thin film with a crystallinity of 60%-70%.

4. The composite copper foil according to claim 3, characterized in that: The area density of the first metal sub-layer is greater than the area density of the second metal sub-layer.

5. The composite copper foil according to claim 2, characterized in that: The first metal sublayer is a nickel-chromium alloy layer or a copper alloy layer.

6. The composite copper foil according to claim 5, characterized in that: The first metal sublayer is a nickel-chromium alloy layer or a nickel-copper alloy layer, and the second metal sublayer is a metal copper layer.

7. The composite copper foil according to claim 6, characterized in that: The thickness of the first metal sublayer is 30nm-100nm, and the thickness of the second metal sublayer is 900nm-1000nm.

8. The composite copper foil according to claim 7, characterized in that: The thickness of the support layer is 3um-8um, the first metal sublayer is a magnetron sputtering layer, and the second metal sublayer is a magnetron sputtering layer.

9. The composite copper foil according to any one of claims 1-2 and 5-8, characterized in that: The support layer is a thin film with a crystallinity of 50%-70%, and the mass of the metal layer is less than that of the support layer.

10. The composite copper foil according to claim 9, characterized in that: The support layer is a film formed by one or more of polyamide, polyimide, polyethylene terephthalate, polybutylene terephthalate, polyethylene naphthalate, polycarbonate, polyethylene, polypropylene, polypropylene, acrylonitrile-butadiene-styrene copolymer, polyvinyl alcohol, polystyrene, polyvinyl chloride, polyvinylidene fluoride, polytetrafluoroethylene, sodium polystyrene sulfonate, polyacetylene, silicone rubber, polyformaldehyde, polyphenylene ether, polyphenylene sulfide, polyethylene glycol, polysulfur nitride polymer materials, polyphenylene, polypyrrole, polyaniline, polythiophene, polypyridine, cellulose, starch, protein, epoxy resin, and phenolic resin.

Citation Information

Cited By

  • Functional copper foil current collector and preparation method and application thereof

    CN119695168A

  • Composite current collector and lithium battery

    CN121123288A